2007
DOI: 10.1016/j.ijgo.2007.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human leukocyte antigen‐G and its correlation with interleukin‐10 expression in cervical carcinoma

Abstract: HLA-G and IL-10 might play an important role in cancer progression of the cervix. High HLA-G mRNA expression may be related to early carcinogenesis since it was associated with early-stage cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…18 Several studies have demonstrated that cervical cancer tissue expressed HLA-G and that its expression correlates with tumor progression. [5][6][7][8]10 In this report, the wildtype HLA-G*01:01:01 allele conferred protection against invasive cancer, whereas variant HLA-G*01:01:02, -G*01:06 and -G*3 0 UTR 14-bp insertion alleles increased cervical cancer risk. The HLA-G*01:01:02 and -G*01:06 alleles both have a synonymous substitution (Proline) at codon 57.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…18 Several studies have demonstrated that cervical cancer tissue expressed HLA-G and that its expression correlates with tumor progression. [5][6][7][8]10 In this report, the wildtype HLA-G*01:01:01 allele conferred protection against invasive cancer, whereas variant HLA-G*01:01:02, -G*01:06 and -G*3 0 UTR 14-bp insertion alleles increased cervical cancer risk. The HLA-G*01:01:02 and -G*01:06 alleles both have a synonymous substitution (Proline) at codon 57.…”
Section: Discussionmentioning
confidence: 53%
“…3,4 However, the link between HLA-G and cervical cancer has been inconsistent and contradictory in the published reports. For instance, HLA-G expression in cervical cancer tissue has been found to be increased, [5][6][7] reduced, 8 or absent. 9,10 HLA-G expression has correlated positively, 6,7 negatively, 5,10 or not at all 11 with cervical disease progression.…”
mentioning
confidence: 99%
“…Results of a previous study demonstrated that human leukocyte antigen-G (HLA-G) and IL-10 mRNA and protein expression in cervical cancer tissues were significantly increased (45), suggesting that HLA-G and IL-10 may play an important role in cervical cancer progression. IL-10 contributes to the impairment of the anti-tumor immune response, either by downregulating human leukocyte antigen Class I expression or by increasing HLA-G expression in human trophoblasts and monocytes (46,47) and certain cancer models, such as lung cancer (48).…”
Section: Il-10 Exerts a Tumor-promoting Effect In Cervical Cancermentioning
confidence: 99%
“…HLA-G is known to inhibit the cytotoxic activity of T lymphocytes and natural killer (NK) cells (49,50), which is associated with cancer development and immune tolerance. High HLA-G mRNA expression may be correlated with early carcinogenesis, since it was associated with early-stage cervical cancer (45). It was demonstrated that HLA-G expression was progressively higher in patients with CIN 1 to CIN 2/3 and was the highest in patients with cervical cancer, suggesting that HLA-G expression in cervical lesions may be associated with carcinogenesis, HPV infection and host immune response (51).…”
Section: Il-10 Exerts a Tumor-promoting Effect In Cervical Cancermentioning
confidence: 99%
“…For example, IL-10 can contribute by increasing HLA-G expression on HLA class Ideficient cells to escape from NK-mediated lysis through interactions with killer inhibitory receptors on NK cells [48,49]. In CeCa lesions, the expression of both HLA-G and IL-10 associated with HPV infection might play an important role in CeCa progression [50,51]. In fact, it has been recently reported that in tissue samples from biopsies derived from patients with CeCa and with loss or downregulation of HLA class I expression, most of the HLA-G-positive cases (87.5%) exhibited upregulation of the IL-10 [52].…”
mentioning
confidence: 99%